6•{[(75-5•13)•5-43]•7}+1=
Răspunsuri la întrebare
Răspuns de
7
6×{[(75-65)×5-43]×7}+1=6×{[10×5-43]×7}+1=6×{[50-43]×7}+1=6×{7×7}+1=6×49+1=294+1=295
ArianaAugustinOwl:
si 6× din fata?
Răspuns de
5
6×{[(75-5×13)×5-43]×7}+1=
=6×{[(75-65)×5-43]×7}+1=
=6×{[10×5-43]×7}+1=
=6×{[50-43]×7}+1=
=6×{7×7}+1
=6×49+1
=294+1
=295
=6×{[(75-65)×5-43]×7}+1=
=6×{[10×5-43]×7}+1=
=6×{[50-43]×7}+1=
=6×{7×7}+1
=6×49+1
=294+1
=295
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă